The role of intrapartum ultrasound combined with free position delivery in the management of abnormal fetal positions during labor - Shanshan Sun; Wenwen Liang; Fen Sun; Meili Yu; Liting Wu; Ting Xu; Cui Zhang; Wenfang Zhuang; Jia Li (BMC Pregnancy and Childbirth)
Abstract Objective To investigate the effectiveness of combining intrapartum ultrasound with free maternal positions in managing abnormal labor, specifically focusing on its impact on delivery outcomes. Methods A retrospective cohort study was conducted on 176 cases of abnormal labor progression in women who attempted vaginal delivery at our hospital from June 2021 to May 2022. Among these, 88 cases were diagnosed with abnormal fetal positions using a combination of intrapartum ultrasound and vaginal examination, and these patients were guided to adopt free maternal positions (experimental group). The control group comprised 88 cases diagnosed with abnormal fetal positions through vaginal examination alone, without any intervention to correct positioning. Maternal and neonatal outcomes, including the duration of the first and second stages of labor, total labor time, cesarean section rates due to failed progression, postpartum hemorrhage, and length of hospital stay, were compared between the two groups. Results The experimental group demonstrated significantly reduced durations of the first and second stages of labor, as well as total labor time, compared to the control group. Furthermore, the rate of cesarean sections due to failed progression was significantly lower in the experimental group. Additionally, the experimental group experienced lower rates of postpartum hemorrhage and shorter hospital stays, with statistically significant differences observed. Conclusion Combining intrapartum ultrasound with free maternal positions shows promise in improving delivery outcomes for women with abnormal fetal positions during labor. These findings highlight the potential benefits of this approach in enhancing the quality of delivery.